ESTABLISHING AN ONLINE PLATFORM IN STATE FAMILY POLYCLINICS (Web of Technology: Multidimensional Research Journal, 2024)
This article is dedicated to creating convenience for doctors and patients, ending excessive bureaucracy and waiting for patients in family polyclinics.